Accuracy of fully automated, quantitative, volumetric measurement of the amount of fibroglandular breast tissue using MRI: correlation with anthropomorphic breast phantoms. (10th March 2017) - Wengert, Georg J.; Pinker, Katja; Helbich, Thomas H.; Vogl, Wolf‐Dieter; Spijker, Sylvia M.; Bickel, Hubert; Polanec, Stephan H.; Baltzer, Pascal A.
Abstract : To demonstrate the accuracy of fully automated, quantitative, volumetric measurement of the amount of fibroglandular breast tissue (FGT), using MRI, and to investigate the impact of different MRI sequences using anthropomorphic breast phantoms as the ground truth. In this study, 10 anthropomorphic breast phantoms that consisted of different known fractions of adipose and protein tissue, which closely resembled normal breast parenchyma, were developed. Anthropomorphic breast phantoms were imaged with a 1.5 T unit (Siemens, Avantofit) using an 18‐channel breast coil. The sequence protocol consisted of an isotropic Dixon sequence (Di), an anisotropic Dixon sequence (Da), and T 1 3D FLASH sequences with and without fat saturation (T1). Fully automated, quantitative, volumetric measurement of FGT for all anthropomorphic phantoms and sequences was performed and correlated with the amounts of fatty and protein components in the phantoms as the ground truth. Fully automated, quantitative, volumetric measurements of FGT with MRI for all sequences ranged from 5.86 to 61.05% (mean 33.36%). The isotropic Dixon sequence yielded the highest accuracy (median 0.51%–0.78%) and precision (median range 0.19%) compared with anisotropic Dixon (median 1.92%–2.09%; median range 0.55%) and T 1 ‐weighted sequences (median 2.54%–2.46%; median range 0.82%). All sequences yielded good correlation with the FGT content of the anthropomorphic phantoms. The best correlation of FGT measurements was identified for Dixon sequences (Di, R 2 = 0.999; Da, R 2 = 0.998) compared with conventional T 1 ‐weighted sequences ( R 2 = 0.971). MRI yields accurate, fully automated, quantitative, volumetric measurements of FGT, an increasingly important and sensitive imaging biomarker for breast cancer risk. Compared with conventional T 1 sequences, Dixon‐type sequences show the highest correlation and reproducibility for automated, quantitative, volumetric FGT measurements using anthropomorphic breast phantoms as the ground truth. Abstract : We demonstrate the accuracy of fully automated quantitative volumetric measurement of the amount of fibroglandular breast tissue using MRI and investigate the impact of different MRI sequences using anthropomorphic breast phantoms as the ground truth.